Color around the Globe: Langston Hughes and Black Internationalism in China. (30th May 2020) - Lai-Henderson, Selina
Abstract: Langston Hughes was the first African American writer to set foot on Chinese soil. Having visited Mexico, Europe, and West Africa before he turned twenty-two, Hughes eventually also made his way to the Soviet Union, Japan, and China in 1933. At the age of thirty-one, he accomplished what none of his contemporaries or predecessors had been able to achieve—to rewrite the public image of African Americans in the Chinese cultural and intellectual imagination. Crucially, his visit to China pushed beyond the limits of black internationalism as he responded to American and European global hegemony through using China as an experimental ground. At a time when the Soviet Union held center stage in communist revolutionary thought, Hughes's Chinese encounters challenged the assumption within the American and African American communities that China was largely irrelevant in the discourse of proletarianism. The internationalist perspectives that he obtained from the sojourn offered him a powerful tool to communicate the struggles of black citizenship at home in a global context. It stimulated a racial consciousness that defied national, geographical, and political boundaries of the US color line.